Effects of probiotic supplementation during pregnancy on metabolic outcomes: A systematic review and meta-analysis of randomized controlled trials. (April 2020) - Masulli, Maria; Vitacolonna, Ester; Fraticelli, Federica; Della Pepa, Giuseppe; Mannucci, Edoardo; Monami, Matteo
Abstract: Aim: To perform a systematic review and meta-analysis of randomized controlled trials (RCTs) to evaluate the effect of probiotics in pregnancy on the incidence of gestational diabetes (GDM) and fasting plasma glucose (FPG). Methods: A MEDLINE, EMBASE, Scopus and Cochrane search (up to May 30th, 2019) was performed to identify RCTs of comparison of probiotics with placebo/active comparators in pregnant women. Principal endpoints were the incidence of GDM and the change of FPG. Other maternal and fetal outcomes were secondary endpoints. Mantel-Haenszel Odds Ratio with 95% CI (MH-OR) was calculated for dichotomous outcomes, whereas standardized differences in means was calculated for continuous variables. (PROSPERO registration CRD42019139889). Findings: A total of 17 RCTs, all versus placebo, was identified. The overall quality of the trials was satisfactory. No effect of probiotics on incidence of GDM (MH-OR: 0.77[0.51, 1.16], p = 0.21, I2:62%) was observed, with a small but significant reduction of FPG (mean difference −1.01 [−1.96, −0.06]mg/dl, p = 0.02, I 2 :46%). Among secondary endpoints, a significant reduction of maternal insulin (both in women with or without diabetes) was observed in the probiotics group. Interpretation: Probiotics during pregnancy do not reduce the incidence of GDM, with a very little (statistically but not clinically significant) reduction of fasting plasma glucose.